THE WILD - Laukkanen, Owen (New York : Underlined, an imprint of Random House Children's Books, 2020)
Seventeen-year-old Dawn and a group of other teens must survive a "wilderness therapy" camp in Washington State as things quickly and drastically go wrong.
Keywords: Adventure therapy -- fiction; Survival -- fiction; Camping -- fiction; Murder -- fiction; Teenagers -- Drug use -- fiction